Evaluating the relationship between socially (dis)advantaged neighbourhoods and customer satisfaction of bus service in London, U.K. (January 2017) - Grisé, Emily; El-Geneidy, Ahmed
Abstract: Affordable and efficient urban public transport is important for the development of a sustainable urban environment. Making sure public transport users are satisfied with the service is a goal many public transport agencies are trying to achieve. Customer satisfaction surveys are often used to monitor customer perceptions of service quality and to determine the relative influence of service attributes on a customer's overall assessment of the service. This study presents a new method to spatially evaluate customer satisfaction survey data through examining satisfaction with bus service across neighbourhoods of varying levels of socio-economic status (SES). Using customer satisfaction survey data collected by Transport for London between 2010 and 2015, multi-level regression modeling is used to estimate the relationship between overall satisfaction and social deprivation of the area in which bus routes were operating. The results indicate lower levels of satisfaction along routes serving low SES neighbourhoods, which appears to be attributed to (1) low satisfaction with service characteristics related to an individual's experience and quality of the bus and (2) conditions of the bus stop and shelter. Findings from this paper shows the importance of including cleanliness and bus internal quality as one of the performance indicators when contracting bus services, to ensure that all customers receive the same quality of service in the region regardless of their SES.